Hubungan Kebisingan terhadap Gangguan Fungsi Pendengaran pada Karyawan Perusahaan X di Cikarang - Kiaranisa A C Tampubolon; Gunterus Evans; Evi U M Situmorang; Lonah Lonah; Hadiyanto Hadiyanto (Journal of Medicine and Health, 2026)
Excessive noise exposure can lead to permanent hearing damage over time. Noise-induced hearing loss (NIHL), caused by occupational noise exposure, is a common health issue. Many studies focus on occupational noise exposure that exceeds exposure limits; yet, few focus on the impact of exposure duration on hearing function. This study aims to analyze the relationship between the duration of noise exposure and loss of hearing function among employees of Company X. This cross-sectional study involved 61 employees of Company X. Company X is a multinational glass company that produces glass and glass ceramics, including syringes, eyeglasses, vials, and ampoules. Data was collected using a noise exposure characteristics questionnaire, a sound level meter for noise level measurement, and audiometry to assess hearing function. Subjects with a prior diagnosis of hearing disorders, hypertension, obesity, and those aged over 65 were excluded from this study. Audiometry results were grouped into categories, with 57 subjects (93.44%) categorized as “normal”, 3 subjects (4.92%) as “mild”, and 1 subject (1.64%) as “moderate”. Chi-square analysis with a P-value of 0.495 (>0.05) indicated that there is no statistically significant relationship between the duration of noise exposure and loss of hearing function among employees of Company X.